Resonant fabrics : listening to urban worlds - Heine, Marvin (Urban studies (Bielefeld, Germany), 2023)
Soundscapes profoundly connect listeners to the places they inhabit and thereby reveal the vibrant and resonant fabrics that lie beneath the delineated spaces of visual representation. Marvin Heine explores and celebrates the many-layered and ambiguously undulating sense- and soundscapes as they shape, and are shaped by urban cultures and particular ways of listening. By examining historical documents, contemporary accounts, and original empirical material through a combination of actor-network-theory, ecology, and sound studies scholarship, he embrace, in a stylistically embodied and often poetic manner, the sonic urban world in all its fragile, ephemeral, yet deeply affective sonority.